Pre-Service EFL Teachers’ Perspectives on AI Integration in Indonesian Urban Schools - S, Kartika (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study explores the perspectives of pre-service EFL teachers on integrating Artificial Intelligence (AI) tools in urban classrooms in Indonesia. As AI increasingly influences language teaching and learning, it is important to understand how future teachers perceive its role, benefits, and challenges in their professional practice. Employing a qualitative descriptive design, the study collected data through an online questionnaire completed by seventy pre-service EFL teachers and follow-up semi-structured interviews with twenty volunteers. The findings revealed that participants generally held positive views of AI integration, highlighting its potential to enhance student motivation, provide immediate feedback, and support differentiated instruction for diverse learners in urban settings. At the same time, their confidence in applying AI remained moderate, reflecting limited training and practical experience. Participants also expressed concerns about infrastructural barriers, institutional support, and ethical issues such as plagiarism and over-reliance on AI outputs. These results suggest that while pre-service EFL teachers see AI as a valuable pedagogical tool, they acknowledge the need for critical awareness and proper preparation. The study implies that teacher education programs should embed AI literacy, pedagogical training, and ethical guidance into curricula to better equip future teachers for AI-enhanced classrooms.